2019
DOI: 10.31219/osf.io/73v4k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commitment and Communication: are we committed to what we mean, or what we say?

Abstract: Communication often involves making a commitment of some sort, for instance to a future action. But what does communicators’ commitment amount to? Specifically, are communicators taken to be committed to what they actually say (what is explicit), or to what they mean (including what is implicit)? Some researchers claim that communicating implicit information leads to a lower attribution of commitment and less accountability than does communicating explicit information. Here we present two studies exploring whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Participants might therefore have treated speakers who only implied to have firsthand evidence in the same way as speakers who explicitly claimed to have such evidence. This finding would be in line with work showing that listeners often take speakers to be committed to their implied meaning (Bonalumi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Participants might therefore have treated speakers who only implied to have firsthand evidence in the same way as speakers who explicitly claimed to have such evidence. This finding would be in line with work showing that listeners often take speakers to be committed to their implied meaning (Bonalumi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, such actions could also be conceived of as nonverbal PCIs 6 . Importantly, although none of the communicative acts investigated in our study involve a believed‐false claim being explicitly expressed, all of them have been discussed as possibly involving commitment (on presuppositions, see Viebahn, 2019; on implicatures, see Meibauer, 2014b; on nonverbal actions, 7 see Bonalumi et al, 2020). Thus, while falling outside the range of the traditional definition of lying, these communicative acts might be classified as lies on the basis of the commitment‐based notion of lying.…”
Section: The Present Researchmentioning
confidence: 94%
“…Furthermore, we assessed whether participants thought that the deceptive claim was calculable from the agent’s statement or action ( calculability ), whether it would be contradictory to explicitly and verbally cancel the deceptive claim conveyed by the statement or action ( non‐cancelability ), and whether it would be redundant to explicitly and verbally reinforce that same claim ( non‐reinforceability ) 13 . Since most previous studies have investigated commitment only in terms of its social consequences (e.g., Bonalumi et al, 2020; Mazzarella et al, 2018), the five additional measures were newly developed for our study on the basis of the theoretical literature on commitment, as well as our own reasoning. In particular, the items were chosen to reflect properties that relate to our notion of commitment, and thus might additionally contribute to explaining participant’s lie judgments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some initial empirical evidence for our claim that conversational implicatures sometimes involve commitment comparable to what is said can be found in Mazzarella et al (2018), whose participants judged agents who explicitly stated a believed-false claim to deserve punishment to the same extent as agents who conveyed the same claim by means of a particularized conversational implicature (although they were less likely to trust agents who explicitly stated a believed-false claim). In addition, Bonalumi et al (2020) found that, at least in some cases, people rely on agents who did not keep a promise that was explicitly stated to the same extent that they rely on agents who did not keep the same promise after conveying it by means of a generalized or particularized conversational implicature, and equally judge such agents to have broken their promise and owe an apology. These findings can be taken as initial evidence for commitment in certain conversational implicatures, since the social consequences of communicating a believed-false claim or breaking a promise should have differed between conversational implicatures and what is said, if the former did indeed involve less commitment.…”
Section: Empirical Findings On Commitment In Conversational Implicaturesmentioning
confidence: 99%